MODERN TRENDS IN TEACHING RUSSIAN AS A FOREIGN LANGUAGE (Web of Discoveries: Journal of Analysis and Inventions, 2024)
This article examines current trends in teaching Russian as a foreign language, focusing on innovative methodologies, technological integration and cultural immersion. The study reviews the literature to identify existing approaches, presents various teaching methods, discusses their results, and provides insight into future directions. It emphasizes the importance of adopting communicative approaches, using technology and promoting cultural immersion to improve the acquisition of Russian as a foreign language.